The poetry of José María Eguren: Tradition and innovation - Martos Carrera, Marco (2018)
The poetry of José María Eguren has been considered alternatively as symbolist or as terminal modernist. As opposed to the revolution that the poetry of César Vallejo means, that of our chosen poet is considered a traditional poetry. This paper tries to show how, knowing well the literary evolution of the genre, Eguren moves towards an absolute modernity which makes him one of the most original poets of tradition in the Spanish language.